Study on the Physical Properties of Deep Coalbed Methane Reservoirs - Wang, Pengxiang; Yu, Wanying; Huang, Juan; Zou, Qiang; Yang, Zhengtao (International Journal of Natural Resources and Environmental Studies, 2025)
China has abundant deep coalbed methane (CBM) resources. Exploration and development efforts this year have revealed that deep CBM reservoirs are characterized by large resource volumes, intact coal structures, high gas content, high gas saturation, and significant development potential. However, significant differences in reservoir properties between deep and shallow coal seams, particularly in pore structure and fracture characteristics, pose challenges. These differences obscure gas migration patterns and make it difficult to establish effective development techniques. To address these challenges, this study examines deep coal reservoir samples from the Turpan-Hami and Junggar Basins. A comprehensive analysis of reservoir properties was conducted using multiple experimental methods. The findings reveal the multi-scale pore development and fracture characteristics of deep coal reservoirs, providing a theoretical basis for further exploration and development of deep CBM resources.